2014
DOI: 10.1155/2014/526719
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Deficiency of Distal Ulna and Dislocation of the Radial Head Treated by Single Bone Forearm Procedure

Abstract: Congenital deficiency of part of distal ulna affecting the distal radio-ulnar joint is a rare disorder. It is even rarer to find the association of proximal radio-ulnar joint dislocation along with distal ulnar deficiency. This type of congenital forearm anomaly is difficult to treat. Conversion to a single bone forearm in the expense of pronation-supination movement is a viable option. By doing so the elbow and wrist can be stabilized; however movement is possible in only one plane. We are describing here a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, Yamazaki et al used the open reduction and ulnar osteotomy for a five-year boy with CRHD in 2007, which demonstrated that the boy obtained significant improvement in elbow motion and had no pain, no osteoarthritic changes at 10 years follow-up 4 . Subsequently, the single bone forearm procedure, single osteotomy, derotation osteotomy are applied to CRHD, which corrects the elbow flexion and motion 6, 7, 8. However, these surgery methods involve complications (infection, hematoma, and thrombosis, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yamazaki et al used the open reduction and ulnar osteotomy for a five-year boy with CRHD in 2007, which demonstrated that the boy obtained significant improvement in elbow motion and had no pain, no osteoarthritic changes at 10 years follow-up 4 . Subsequently, the single bone forearm procedure, single osteotomy, derotation osteotomy are applied to CRHD, which corrects the elbow flexion and motion 6, 7, 8. However, these surgery methods involve complications (infection, hematoma, and thrombosis, etc.)…”
Section: Introductionmentioning
confidence: 99%